Beyond the affinity for protein kinase C: exploring 2-phenyl-3-hydroxypropyl pivalate analogues as C1 domain-targeting ligands1. Issue 4 (10th April 2015) - Rossi, Daniela; Talman, Virpi; Gennäs, Gustav Boije Af; Marra, Annamaria; Picconi, Pietro; Nasti, Rita; Serra, Massimo; Ann, Jihyae; Amadio, Marialaura; Pascale, Alessia; Tuominen, Raimo K.; Yli-Kauhaluoma, Jari; et al.
<x xml:space="preserve">Abstract</x> Over the past fifteen years, we reported the design and synthesis of different series of compounds targeting the C1 domain of protein kinase C (PKC) that were based on various templates.